HUBUNGAN STRES AKADEMIK DENGAN KECENDERUNGAN BERMAI GAME ONLINE PADA MAHASISWA UNIVERSITAS MALAHAYATI BANDAR LAMPUNG TAHUN 2021 - Octa Reni Setiawati; Ismalia Husna; Sri Maria Puji Lestari; Gustav Abitri Sentosa (Medula, 2022)
Education is currently experiencing many obstacles and one of them is academic stress experienced by students. Students who experience academic stress will look for ways to reduce academic stress by playing online games. Students who play online games too often will tend to play online games. This type of research uses questionnaire measuring instruments with quantitative studies of observational analytics using probalitity sampling methods with total sampling techniques. The sample in this study was students of the Faculty of Medicine Class of 2019 Malahayati University Bandar Lampung amounted to 103 people. Analyze the data using spearsmans correlation test. In students of the university's medical faculty, even in bandar lampung class of 2019, almost some students experienced academic stress with a total of 57 people with a percentage (56.4%). Almost some students experience a tendency to play online games with a total of 47 people with a percentage (46.5%). There is a meaningful relationship between academic stress and a tendency to play online games (p-value 0.000). There is a relationship of academic stress with the tendency to play online games in students of Malahayati University Bandar Lampung in 2021.